2005
DOI: 10.1002/pmic.200401240
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and protein profiling of AGS gastric epithelial cells upon infection with Helicobacter pylori

Abstract: Helicobacter pylori, one of the most common bacterial pathogens, colonizes the human stomach and causes a variety of gastric diseases. This pathogen elicits a range of phenotypic responses in infected cultured AGS gastric epithelial cells, including expression of proinflammatory genes and changes in the actin cytoskeleton. Some of these responses are mediated by the type IV secretion system (T4SS) encoded by the cag pathogenicity island. We have used two global approaches, namely 2-DE combined with PMF and cDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
24
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 83 publications
1
24
0
1
Order By: Relevance
“…An additional property in interaction with the extracellular matrix of infected host cells was also proposed by Backert et al (71). High levels of EF-Tu expression in HP isolates from GC patients have been reported (32,62).…”
mentioning
confidence: 70%
“…An additional property in interaction with the extracellular matrix of infected host cells was also proposed by Backert et al (71). High levels of EF-Tu expression in HP isolates from GC patients have been reported (32,62).…”
mentioning
confidence: 70%
“…Transcriptome studies on human and animal host response have demonstrated that H. pylori targets specific host factors involved mainly in cytoskeletal changes, activation of different signal transduction pathways, change in cell morphology, cytokine induction, alteration of cell proliferation pattern and apoptosis (6)(7)(8)(9)(10)(11)(12). In the present study, the global host gene expression profiling in response to chronically…”
mentioning
confidence: 79%
“…These include acute gastritis [1][2][3] , chronic atrophic gastritis [3,4] , intestinal metaplasia [5] , peptic ulcer [6,7] , mucosal associated lymphoid tissue (MALT) lymphoma [8] , and other disorders [9,10] . Although many epidemiological studies and animal models revealed close association between gastric cancer and H pylori infection [11][12][13] , there have been few studies that report on genetic alterations suggestive of gastric carcinogenesis associated with chronic H pylori infection [14][15][16][17] . Previously, we reported the expression of p53, a product of oncosupressor-gene and cell cycle regulator, in the H pylori-infected human gastric mucosa [18] as well as in a Japanese monkey model [19] .…”
Section: Introductionmentioning
confidence: 99%